2000
DOI: 10.1002/1096-8628(20001009)96:5<632::aid-ajmg8>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A genome screen of maximum number of drinks as an alcoholism phenotype

Abstract: The Collaborative Study on the Genetics of Alcoholism (COGA) is a multicenter research program to detect and map susceptibility genes for alcohol dependence and related phenotypes. The measure M of "maximum number of drinks consumed in a 24-hour period" is closely related to alcoholism diagnosis in this dataset and provides a quantitative measure to grade nonalcoholic individuals. Twin studies have shown log(M) to have a heritability of approximately 50%. Genome screens for this trait were performed in two dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
166
2
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 197 publications
(180 citation statements)
references
References 37 publications
11
166
2
1
Order By: Relevance
“…It is also worth noting that some linkage peaks previously identified in COGA on chromosome 4 and 7 (Saccone et al, 2000;Saccone et al, 2005;Foroud et al, 2000;Reich et al, 1998;Nurnberger, Jr. et al, 2001) were not identified in the current study. Those peaks harbor genes such as GABRA2, ADH (on chromosome 4) and CHRM2 and hTAS2R16 (on chromosome 7), which have subsequently found to be associated with risk for alcoholism Wang et al, 2004;Edenberg et al, 2006a;Hinrichs et al, 2006).…”
Section: Discussioncontrasting
confidence: 66%
“…It is also worth noting that some linkage peaks previously identified in COGA on chromosome 4 and 7 (Saccone et al, 2000;Saccone et al, 2005;Foroud et al, 2000;Reich et al, 1998;Nurnberger, Jr. et al, 2001) were not identified in the current study. Those peaks harbor genes such as GABRA2, ADH (on chromosome 4) and CHRM2 and hTAS2R16 (on chromosome 7), which have subsequently found to be associated with risk for alcoholism Wang et al, 2004;Edenberg et al, 2006a;Hinrichs et al, 2006).…”
Section: Discussioncontrasting
confidence: 66%
“…The positive region for ND on chromosome 2 has been linked to alcohol dependence in the COGA sample 38,39 and in the Oregon Smoking Families study. 40 The linkage region for ND on chromosome 4 detected in the EA sample of the MSTF cohort has also been linked to alcohol dependence in three independent samples 35,38,40,41 and to polysubstance abuse. 36,37 Moreover, two recent large-scale association studies also provide partial support to some of our linkage findings.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in several of the genes in this gene cluster are clearly associated with a decreased risk of alcoholism (41,42). This region also displays linkage to an alcohol-related phenotype, the maximum number of drinks consumed in a 24-h period (43). It will be interesting to determine whether variation in the human ␣-synuclein gene is associated with an alcohol-related phenotype.…”
Section: Figmentioning
confidence: 99%